2017
DOI: 10.1038/s41598-017-15142-w
|View full text |Cite
|
Sign up to set email alerts
|

Specific Targeting of Melanotic Cells with Peptide Ligated Photosensitizers for Photodynamic Therapy

Abstract: A strategy combining covalent conjugation of photosensitizers to a peptide ligand directed to the melanocortin 1 (MC1) receptor with the application of sequential LED light dosage at near-IR wavelengths was developed to achieve specific cytotoxicity to melanocytes and melanoma (MEL) with minimal collateral damage to surrounding cells such as keratinocytes (KER). The specific killing of melanotic cells by targeted photodynamic therapy (PDT) described in this study holds promise as a potentially effective adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…cancer cell lines where light-activation is amenable. 24,25 This could be a photodynamic therapy using a non-invasive approach that can also be coupled with extremely high 3D optical precision. Since the entry of the PI is on a relatively short time scale compared to the time of cell division, the cell has insufficient time to adopt programmed cell death (apoptosis).…”
Section: Resultsmentioning
confidence: 99%
“…cancer cell lines where light-activation is amenable. 24,25 This could be a photodynamic therapy using a non-invasive approach that can also be coupled with extremely high 3D optical precision. Since the entry of the PI is on a relatively short time scale compared to the time of cell division, the cell has insufficient time to adopt programmed cell death (apoptosis).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that DOC/peptide NPs can inhibit tumor growth compared to that in the group without peptide, demonstrating the effectiveness of this bifunctional peptide-based vehicle. [87] The resulting peptide was conjugated to the photosensitizer δ-aminolevulinic acid (ALA) and targeted melanoma cells. [82] Hong et al synthesized a cRGD peptidepyropheophorbide-a (Pyro) conjugate for PDT.…”
Section: Tumor-targeting Peptidesmentioning
confidence: 99%
“…For PDT, an octapeptide derivative of a chelator (DOTA)-modified α-melanocyte-stimulating hormone (α-MSH) was bound specifically to the melanocortin 1 (MC1) receptor. [87] The resulting peptide was conjugated to the photosensitizer δ-aminolevulinic acid (ALA) and targeted melanoma cells. Van Lier et al synthesized several conjugates using bombesin (BBN) (Tyr-Gln-ArgLeu-Gly-Asn-Gln-Trp-Ala-Val-Gly-His-Leu-Met-NH2) and phthalocyanine to target the gastrin-releasing peptide receptors.…”
Section: Tumor-targeting Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside high production costs, heterogeneity of samples can result in poor reproducibility. Recently, the targeting ability of peptides has increased in popularity [10][11][12][13][14][15] as these chemically synthesised molecules can overcome many of the disadvantages that proteins present, while still maintaining selectivity towards the desired target.…”
mentioning
confidence: 99%